Ultrasound-detected inflammation is more common in clinically manifest hand osteoarthritis than in painless bony enlarged finger joints: subanalysis of the population-based Bruneck study. (May 2022) - Gasperi, Nina; Schreiber, Nikolaus; Bosch, Philipp; Adinolfi, Antonella; Kleyer, Arnd; Hagen, Melanie; Gasperi, Christiane; Weger, Martin; Kiechl, Stefan; Willeit, Johann; Schett, Georg; Iagnocco, Annamaria; et al.
Purpose: The aim of this article is to examine the extent of structural and inflammatory lesions by ultrasound in elderly subjects with hand osteoarthritis (HOA) fulfilling the ACR classification criteria (Group A), in subjects with painless enlarged finger joints (Group B), and in individuals without clinical abnormalities at hands (Group C). Methods: This study was nested within the population-based, prospective Bruneck study; 293 subjects of ⩾65 years of age were assessed. Clinical and ultrasound assessment was conducted at wrists and finger joints. Gray scale synovitis (GSS), Power Doppler (PD), osteophytes, and erosions were scored semiquantitatively (0–3). The Short Form Score for the Assessment and Quantification of Chronic Rheumatic Affections of the Hands (SF-SACRAH), the Health Assessment Questionnaire (HAQ), and the Functional Index for Hand Osteoarthritis (FIHOA) were retrieved. Results: Most subjects had ⩾1 ultrasound abnormality, of which osteophytes were the most prevalent finding in all groups (Group A: 100%, Group B: 99.4%, and Group C: 93.9%). GSS and PD-signals were more common in Group A than in Group B (94% versus 67% and 33% versus 13%, respectively). In Group C, GSS was observed in 39.4% of subjects. In subjects with HOA, the SF-SACRAH correlated with osteophyte scores (corrcoeff = 0.48), and the FIHOA correlated with the osteophyte (corrcoeff = 0.42) and PD scores (corrcoeff = 0.33). Conclusion: GSS and PD were more frequent in patients with symptomatic HOA than in cases with painless bony enlargements and subjects without clinical joint abnormalities. Functional restriction in HOA is associated with structural and inflammatory ultrasound changes.